Effect of tin-doped indium oxide film on electrodeposition of ZnO nanostructures. (14th November 2015) - Pruna, A.; Pullini, D.; Tamvakos, D.; Tamvakos, A.; Busquets-Mataix, D.
Abstract : Surface studies are reported for the deposition of ZnO nanostructures by one-step electrodeposition method. The electrosynthesis was perfomed at the surface of tin doped indium oxide coated glass substrates in the absence of any buffer layer. The growth of ZnO nanostructures was investigated with the morphology of substrate and the deposition mode. Combined nucleation mode was observed for the ZnO independently of substrate. The results indicated the growth, morphology and density of the ZnO nanostructures are markedly influenced by both the substrate and the deposition conditions. It was observed the ZnO formation is defect site driven in case of galvanostatic deposition mode, while in case of potentiostatic deposition mode, it is dependent on the roughness of the substrate.